Hubungan Antara Iklim Kelas dan Kemandirian Belajar Terhadap Hasil Belajar Matematika - Sheril Agnuedella; Nina Agustyaningrum (JURNAL PENA EDUKASI, 2021)
Abstract: This research aims to determine: (1) Correlation of classroom climate to the result mathematic lesson in 8 grade of SMPN 30 at Batam, (2) Correlation of independence learning to the result mathematic lesson in 8 grade of SMPN 30 at Batam, (3) The correlation of classroom climate and independence of learning as simultaneously on the result of mathematic lesson in 8 grade of SMPN 30 Batam. This used quantitative research with the correlation method. The population of this research were 222 respondents, which is the whole students in 8 grade on SMPN 30 Batam. The Sampling of this survey is Simple Random Sampling. The draft instrument this survey of documentation and questionnaire that had been tested for validity and reliability. The result of the analytical test can we conclude: (1) There is a significant correlation of classroom climate toward the result of mathematic lesson in 8 grade of SMPN 30 Batam with the coefficient correlation value 0.796, (2) There is a significant correlation of independence learning toward the result of mathematic lesson in 8 grade of SMPN 30 Batam with the coefficient correlation value 0.496, (3)  Simultaneously indicating that there is the is a significant correlation of classroom climate and independence of learning as simultaneously on the result of mathematic lesson in 8 grade of SMPN 30 Batam with the coefficient correlation value 0.798 Keywords: classroom climate; independence of learning; math learning results.  Abstrak:i Penelitian ini bertujuan untuk mengetahui: (1) Hubungan iklim kelas terhadap hasil belajar matematika kelas VIII SMP Negeri 30 Batam, (2) Hubungan kemandirian belajar terhadap hasil belajar matematika kelas VIII SMP Negeri 30 Batam, (3) Hubungan iklim kelas dan kemandirian belajar secara bersama-sama terhadap hasil belajar matematika kelas VIII SMP Negeri 30 Batam. Penelitian ini merupakan penelitian kuantitatif dengan metode korelasi. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 30 Batam sebanyak 222 siswa. Pengambilan sampel dilakukan dengan teknik simple random sampling. Instrumen dalam penelitian ini berupa dokumentasi dan angket yang sudah di uji validitas dan reliabilitasnya. Hasil analisis menunjukkan bahwa: (1) Terdapat hubungan yang signifikan antara iklim kelas dengan hasil belajar matematika siswa kelas VIII SMP Negeri 30 Batam dengan koefisien korelasi sebesar 0,796, (2) Terdapat hubungan yang signifikan antara kemandirian belajar dengan hasil belajar matematika siswa kelas VIII SMP Negeri 30 Batam dengan koefisien korelasi sebesar 0,496, (3) Terdapat hubungan yang signifikan antara iklim kelas dan kemandirian belajar secara bersama-sama terhadap hasil belajar matematika siswa kelas VIII SMP Negeri 30 Batam dengan koefisen korelasi berganda sebesar 0,798. Kata Kunci: hasil belajar matematika; iklim kelas; kemandirian belajar.